Phytoplankton and Bacterial Communities in South Harbour, Manila Bay, Philippines - Rhodora V Azanza; Nero M Austero; Jenelle Clarisse R. Dungca; Frenchly Joyce O. Caspe; Lidita Khandeparker (ASEAN Journal on Science and Technology for Development, 2018)
In line with the ASEAN-India project “Extent of Transfer of Alien Invasive Organisms in South/Southeast Asia via Shipping”, phytoplankton and bacterial communities in the waters off South Harbour, Manila Bay were investigated. Sampling was done in July and August 2012 and in April and May 2013. A total of 67 phytoplankton species including 29 diatoms and 38 dinoflagellates were identified. Potentially toxic Pseudo-nitzschia spp. were among the diatoms found as well as dinoflagellates Alexandrium spp., and Gymnodinium spp. The diatom Skeletonema costatum appeared to be the dominant species in July and August 2012, whereas Chaetoceros spp. constituted over 85% of the total phytoplankton assemblage in April and May 2013. Mean bacterialabundance ranged from 9.53 x 102–3.18 x 105 cells/mL in July 2012. In addition, 93 bacterial isolates were identified using 16S rDNA, several of which belonged to the following phyla: Actinobacteria, Bacteriodetes, Firmicutes, and Proteobacteria; whereas, others were determined as uncultured bacterial clones. These results will serve as a valuable baseline for future studies on phytoplankton and bacterial community structure in Manila Bay.